Review of Yoga Minds, Writing Bodies: Contemplative Writing Pedagogy by Christy Wenger - Matthew Overstreet (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
When given the chance to review a book for JAEPL, I immediately suggested Christy Wenger’s Yoga Minds, Writing Bodies. Not only is this a book I highly respect, but one of its themes is perhaps more relevant than ever today, some six years after its publication.
Keywords: JAEPL